2022
DOI: 10.1007/s00259-021-05674-9
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast activation protein imaging in reperfused ST-elevation myocardial infarction: comparison with cardiac magnetic resonance imaging

Abstract: The goals were to explore the correlation of 18 F-labeled broblast activation protein inhibitor (FAPI) and cardiovascular magnetic resonance (CMR) parameters in ST-elevation myocardial infarction (STEMI) patients with successful primary percutaneous coronary intervention (PPCI) and to investigate the value of FAPI imaging in predicting cardiac functional recovery. MethodsFourteen rst-time STEMI patients (11 men, mean age: 62 ± 11 years) after PPCI were prospectively recruited. All patients underwent baseline F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 36 publications
2
21
1
Order By: Relevance
“…There may be a simultaneous dysregulation of metabolic and hypertrophic pathways in the human heart responsible for the increase in FAPI uptake. Previous studies demonstrated circulating FAP and TGF-β1 levels significantly declined (31). The inconsistency between tissue-level and circulating-level biomarkers raises the possibility that peripheral biomarkers may not be reliable indicators of tissue status (39).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There may be a simultaneous dysregulation of metabolic and hypertrophic pathways in the human heart responsible for the increase in FAPI uptake. Previous studies demonstrated circulating FAP and TGF-β1 levels significantly declined (31). The inconsistency between tissue-level and circulating-level biomarkers raises the possibility that peripheral biomarkers may not be reliable indicators of tissue status (39).…”
Section: Discussionmentioning
confidence: 97%
“…Cardiac FAP activation has been reported in a variety of pathological conditions (3,(28)(29)(30). Myocardial fibrosis after myocardial infarction has been reported in several studies (5,9,11,31). Radiotracer delivery may be inadequate in infarcted areas, explaining this pattern of tracer uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, radiolabeled fibroblast activation protein inhibitor (FAPI)-targeting tracers have been developed to detect activated fibroblasts [4]. Both our research and that of other groups have demonstrated that FAPI imaging is feasible for the assessment of pathological fibroblast activation in ventricles [5,6]. If this technique is also feasible in the atriums, the initial reversible phase of atrial fibrosis could be detected, thus guiding treatments aimed at reversing the pathological fibrotic process.…”
Section: Introductionmentioning
confidence: 84%
“…Accumulating studies of nuclear medicine have paid great attention to fibrosis-specific molecular imaging. Several imaging methods, such as collagelin labeling (e.g., using 99 mTc-labeled collagelin), activated fibroblast and myofibroblast labeling (e.g., using 68 Ga-labeled or 18 F-labeled fibroblast activation protein inhibitor) techniques, have emerged (6,77,78). Though promising, more studies are required to validate its detection accuracy in humans.…”
Section: Nuclear Imagingmentioning
confidence: 99%